Biomechanical Evaluation of the Pedicle Screw Insertion Depth Effect on Screw Stability Under Cyclic Loading and Subsequent Pullout. Issue 3 (April 2015) - Karami, Kristophe J.; Buckenmeyer, Laura E.; Kiapour, Ata M.; Kelkar, Prashant S.; Goel, Vijay K.; Demetropoulos, Constantine K.; Soo, Teck M.
Abstract : Study Design: A biomechanical ex vivo study of the human lumbar spine. Objective: To evaluate the effects of transpedicular screw insertion depth on overall screw stability and pullout strength following cyclic loading in the osteoporotic lumbar spine. Summary of Background Data: Although much is known about the clinical outcomes of spinal fusion, questions remain in our understanding of the biomechanical strength of lumbar pedicle screw fixation as it relates to screw sizing and placement. Biomechanical analyses examining ideal pedicle screw depth with current pedicle screw technology are limited. In the osteoporotic spine, optimized pedicle screw insertion depth may improve construct strength, decreasing the risk of loosening or pullout. Methods: A total of 100 pedicles from 10 osteoporotic lumbar spines were randomly instrumented with pedicle screws in mid-body, pericortical, and bicortical depths. Instrumented specimens underwent cyclic loading (5000 cycles of ±2 N m pure flexion moment) and subsequent pullout. Screw loosening, failure loads, and energy absorption were calculated. Results: Cyclic loading significantly ( P <0.001) reduced screw-bone angular stiffness between prefatigue and postfatigue conditions by 25.6%±17.9% (mid-body), 20.8%±14.4% (pericortical), and 14.0%±13.0% (bicortical). Increased insertion depth resulted in lower levels of reduction in angular stiffness, which was only significant between mid-body and bicortical screws ( P =0.009). Pullout force and energy of 583±306 N and 1.75±1.98 N m (mid-body), 713±321 N and 2.40±1.79 N m (pericortical), and 797±285 N and 2.97±2.33 N m (bicortical) were observed, respectively. Increased insertion depth resulted in higher magnitudes of both pullout force and energy, which was significant only for pullout force between mid-body and bicortical screws ( P =0.005). Conclusion: Although increased screw depth led to increased fixation and decreased loosening, additional purchase of the stiff anterior cortex is essential to reach superior screw-bone construct stability and stiffness.